Accelerating rare disease detection: an experience of multidisciplinary team model in undiagnosed diseases program in a children’s hospital - Shi, Yu; Miao, Shijian; Yuan, Yuan; Fu, Yang; Sun, Chengjun; Wang, Hongsheng; Ge, MengMeng; Li, Dongyun; Shen, Guomei; Gao, Xuan; Zhai, Xiaowen (Frontiers in Public Health, 2024)
Background: A definite diagnosis goes undiscovered for a percentage of children with undiagnosed disorders, with significant medical, psychological, and social effects. Other than specialized clinical centers, exceptional molecular studies, common procedures, and devoted activities at the national and international levels, children with complex undiagnosed disorders require innovative approaches.In March 2016, Children's hospital of Fudan university represented the Children's Undiagnosed Diseases Program (UDP). The purpose of this study is to describe the project findings and underline the critical significance of multidisciplinary teamwork in China's undiagnosed rare illnesses program. We investigated the 758 cases in our UDP system retrospectively. Demographic information, laboratory test results, and genetic information were gathered.Results: Between January 2017 and December 2021, 758 cases were examined. Males made up 436 (57.5%) of the total. Over half of the patients were children under the age of five. The average patient course time preceding admission to UDP was 6.0 months (95% CI 10.512.6). These patients visited an average of 1.8 clinics during their diagnostic journey.Except for 69 individuals (90.9%), all had more than one presenting symptom in various organs: 460 (60.7%) had neurology difficulties, 151 (19.9%) had endocrine problems, and 141 (18.6%) had immunology problems. UDP has a diagnosis rate of 61.3%. Genetic testing was performed on 469 of the 758 patients, for a genetic diagnosis rate of 15.8%.The UDP method has a sensitivity of 94.5%, a specificity of 86.4%, a positive predictive value of 92.8%, and an negative predictive value of 89.5%.Our UDP targets an unmet need, namely the diagnosis of patients with complicated, multisystem illnesses. Using a multidisciplinary team model approach, this UDP pilot study achieved a reasonable diagnosis 3 success rate, increasing the possibility of more diagnoses and new scientific discoveries of difficult and rare diseases.